E-Invoicing Vs. The Expected Changes in Entrepreneur Accounting Services - Cyryl KOTYLA (Communications of International Proceedings, 2023)
The study aims to determine the expected changes in accounting services for entrepreneurs relying on the services of third-party accounting firms, in connection with the introduction of mandatory electronic invoicing. The literature lacks studies on the changes expected by entrepreneurs in the services of accounting offices, relative to the introduction of mandatory e-invoicing. The conducted study has allowed a preliminary identification of the entrepreneurs’ expectations towards accounting offices, in connection with the introduction of e-invoicing, and thus indication of further research directions aimed at prepping businesses and accounting offices for the implementation of mandatory e-invoicing. Entrepreneurs expect e-invoicing to eliminate the need to deliver paper invoices to accounting and reduce the frequency of accounting office visits. Accounting offices are instead to be given access to XML files in their clients' e-invoicing systems, from where the transaction data can be downloaded automatically into the financial and accounting systems. The research entails a qualitative descriptive study incorporating the case study method as the research approach and is is preliminary in nature (a pilot study). However, the study requires a supplementary quantitative study conducted on a much larger, randomly selected sample, as well as a separate study conducted among accounting offices.
Keywords: e-invoicing; e-accounting; KSeF; VAT gap